2020
DOI: 10.1186/s12885-020-06781-w
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion as a prognostic factor for intrahepatic cholangiocarcinoma after curative resection and a potential indication for postoperative chemotherapy: a retrospective cohort study

Abstract: Background: Cholangiocarcinoma (CCA) is a type of malignant tumor that arises from the epithelium of the bile ducts. CCA can invade and metastasize to other tissues in a variety of ways but distal skeletal muscle metastasis is extremely rare. Case presentation: We present a case of metastasis of the right thigh from cholangiocarcinoma. Conclusion: Perineural invasion may be a pathway of distant metastasis in CCA that has not been not widely recognized. We advocate the complete removal of tumor with dissection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
(40 reference statements)
1
26
0
Order By: Relevance
“…Perineural invasion is quite common in EHCCA, reported occurring in about 80% of patients with EHCCA [13] . Zhang et al [14] treated the perineural invasion as an independent risk factor in cholangiocarcinoma, presenting worse recurrence and survival outcomes. Perineural invasion is an important pathological feature of cholangiocarcinoma, characterized by tumor cells surrounding nerve bers and entering the perineurium or neural fascicles.…”
Section: Discussionmentioning
confidence: 99%
“…Perineural invasion is quite common in EHCCA, reported occurring in about 80% of patients with EHCCA [13] . Zhang et al [14] treated the perineural invasion as an independent risk factor in cholangiocarcinoma, presenting worse recurrence and survival outcomes. Perineural invasion is an important pathological feature of cholangiocarcinoma, characterized by tumor cells surrounding nerve bers and entering the perineurium or neural fascicles.…”
Section: Discussionmentioning
confidence: 99%
“…ICC patients underwent curative hepatectomy between January 2013 and December 2017 in Xiangya hospital, Central South University, were retrospectively analyzed. Exclusion criteria were as followed: (1) pathology did not support the diagnosis of ICC, (2) recurrence of ICC, (3) received an anti-tumor therapy before resection, (4) suffering from infectious diseases before resection, (5) suffering from autoimmune diseases or immunodeficiency diseases, (6) patients who died of postoperative complications or reasons other than ICC, (7) R1 or R2 resection, (8) hilar type of ICC, and (9) incomplete clinical data. The ethics committee of Xiangya Hospital of Central South University approved this study.…”
Section: Study Cohortmentioning
confidence: 99%
“…4 Many researches were performed and found various signi cant risk factors in ICC, helping the management of ICC patients. 5,6 Meantime, increasing evidences have shown that in ammation and in ammatory biomarkers are signi cant factors in tumor microenvironment, thus promoting proliferation, angiogenesis and metastasis by various in ammatory cells and cytokines. 7 In recent years, multiple in ammatory biomarkers were investigated for predicting the prognosis of patients with various cancer, including neutrophil-tolymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), systemic immune-in ammation index (SII).…”
Section: Introductionmentioning
confidence: 99%